Sickle Cell Trait Presenting as Unilateral Proliferative Retinopathy and Macular Thinning in a Pregnant Woman - Sepideh Ghods; Elias Khalili Pour; Hooshang Faghihi; Golnaz Gharehbaghi; Ahmad Mirshahi; Fariba Ghassemi; Bahman Inanloo; Hamid Riazi-Esfahani (Case Reports in Ophthalmological Medicine)
Background. To report a case of a pregnant woman with sickle cell trait (SCT) who presented with unilateral proliferative sickle cell retinopathy. Case Presentation. A 26-year-old otherwise healthy pregnant woman presented with the complaint of visual loss in her left eye. The funduscopic examination showed vitreous hemorrhage, sea fan neovascularization, and pale optic disc. Optical coherence tomography revealed macular inner retinal layer thinning and foveal splaying (saucerization of the foveal pit). The investigations, including hemoglobin electrophoresis, verified the diagnosis of sickle cell trait. Blood pressure, fasting blood glucose tests, and tuberculin skin tests were normal. We treated the patient by peripheral retinal photocoagulation over the area of nonperfusion. Conclusion. Even though the sickle cell trait is generally considered as a milder form of sickle cell disease without severe retinal manifestations, pregnancy should be considered as a trigger that can induce proliferative changes and foveal splaying in this group of patients.